Climatic and Oceanographic Controls on Coral Bleaching Conditions in the Maldivian Region - De Falco, Chiara; Bracco, Annalisa; Pasquero, Claudia (Frontiers in Marine Science, 2020)
The frequency of coral bleaching events has been increasing in recent decades, due to the temperature rise registered in most ocean regions. Their occurrence in the Maldivian Archipelago has been observed in the months following the peak of strong El Niño events. Bleaching has not been uniform, and some reefs have been only marginally impacted. Here, we use satellite observations and a regional ocean model to explore the spatial and temporal variability of sea surface temperatures (SST), and quantify the relative magnitude of ENSO-related episodes with respect to the recent warming. In line with other studies, it is confirmed that the long term trend in SST significantly increases the frequency of stress conditions for the Maldivian corals. It is also found that the interaction between currents and the steep bathymetry is responsible for a local cooling of about 0.2°C in the Archipelago during the warmest season, with respect to the surrounding waters. This cooling largely reduces the frequency of mortality conditions.